The role of folate in the management of insulin resistance in adults : a systematic review - Theresia Adareth (Indonesian Nutrition Association, 2023)
Insulin resistance (IR) is one of the main risk factors for type 2 diabetes. IR employs a heavy economic burden, and the prevalence rate of IR in Indonesia is high. Homeostasis model of assessment-insulin resistance (HOMA-IR) is proven to be a great clinical tool to assess IR. Nutrition intervention should be the primary focus in treating IR. Folate is proven to be effective in lowering homocysteine concentrations, which is one of the risk factors for IR. This study aimed to summarize the role of folate in the management of IR in adults.